2019
DOI: 10.1186/s12966-019-0860-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a healthy lifestyle and all-cause and cause-specific mortality in Chinese adults: a 10-year prospective study of 0.5 million people

Abstract: BackgroundAdherence to a healthy lifestyle is associated with substantially lower risks of mortality from all causes, cardiovascular diseases, and cancer in white populations. However, little is known about the health benefits among non-white populations. Also, no previous studies have focused on respiratory disease mortality in both white and non-white populations. We assessed the relationships between a combination of healthy lifestyle factors and multiple death outcomes in Chinese adults.MethodsThis study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 35 publications
7
69
0
2
Order By: Relevance
“…The 20-year prospective study included a relatively large sample size examining the association between high blood pressure and mortality from CVDs in rural China. The CVDs deaths in the current study were comparable with several previous studies in China 13 32. A previous study suggested a north-south gradient in the mortality of CVDs due to the difference in the prevalence of hypertension in China 33.…”
Section: Discussionsupporting
confidence: 90%
“…The 20-year prospective study included a relatively large sample size examining the association between high blood pressure and mortality from CVDs in rural China. The CVDs deaths in the current study were comparable with several previous studies in China 13 32. A previous study suggested a north-south gradient in the mortality of CVDs due to the difference in the prevalence of hypertension in China 33.…”
Section: Discussionsupporting
confidence: 90%
“…Our results add to the evidence that a healthy lifestyle is associated with cardiovascular health and inversely associated with all-cause mortality [ 21 , 22 , 26 , 46 50 ]. In the large SUN cohort, comprising university graduates in Spain, a better adherence to a joint healthy lifestyle was associated with lower risk of hypertension [ 49 ], MS [ 51 ], and CVD [ 23 ].…”
Section: Discussionsupporting
confidence: 78%
“…We multiplied the drinking frequency by quantity consumed per drinking day to compute the weekly consumption of alcohol. As in previous literatures from other investigators (Xi et al, 2017;Zhu et al, 2019), we defined heavy drinking as consuming more than 14 drinks per week for men (7 for women). Physical activity was estimated based on recall of a typical week, by asking the frequency and time spent on leisure-time exercise, such as walking, dancing, jogging or playing sports.…”
Section: Behaviors Variablesmentioning
confidence: 99%